2015
DOI: 10.1002/jeab.171
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced behavioral variability: Working towards an understanding of its behavioral mechanisms

Abstract: There is disagreement about how to characterize the environment-behavior relations involved in the reinforcement of behavioral variability. The present research examined some of these issues using food-maintained, 4-peck sequences in pigeons. Experiment 1 evaluated the claim that behavioral variability is not reinforced directly but, rather, is the byproduct of changing over within sequences. Considerably higher levels of behavioral variation occurred under a relative-frequency threshold contingency than under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…In other words, reinforcers delivered following left key pecking may also strengthen right key pecking, and it may be difficult for a pigeon to exactly replicate a previous sequence, especially when longer sequences are used. However, when Doughty and Galizio () arranged for shorter sequences than used in the prior experiments, reinforcing switches was insufficient to produce variable responding. Additionally, the results of the present study provide evidence that at least in some cases, increased switching does not lead to an increase in behavioral variability (see Experiment 3).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In other words, reinforcers delivered following left key pecking may also strengthen right key pecking, and it may be difficult for a pigeon to exactly replicate a previous sequence, especially when longer sequences are used. However, when Doughty and Galizio () arranged for shorter sequences than used in the prior experiments, reinforcing switches was insufficient to produce variable responding. Additionally, the results of the present study provide evidence that at least in some cases, increased switching does not lead to an increase in behavioral variability (see Experiment 3).…”
Section: Discussionmentioning
confidence: 89%
“…Examining relative frequency distributions may provide a more complete measure of behavioral variability than U-value alone. Relative frequency distribution analyses involve examining the incidence of every possible response alternative (e.g., Doughty & Galizio, 2015;Doughty et al, 2013;Machado, 1997;Neuringer et al, 2001;Odum et al, 2006). Relative frequency distributions reveal whether any response options have been systematically omitted, which would affect U-value calculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several later experiments have shown that variability, normally measured as the dispersion of different sequences, are higher when a variability contingency is in effect, than when it is not (e.g., Denney & Neuringer, 1998;Kong, McEwan, Bizo, & Foster, 2019;Miller & Neuringer, 2000). This finding is highly reliable, and the interpretation of "direct reinforcement of variability" and "variability as an operant dimension" has been widely accepted (e.g., Catania, 2013;Doughty & Galizio, 2015;Dracobly, Dozier, Briggs, & Juanico, 2017;Lee, Sturmey, & Fields, 2007;Locey & Rachlin, 2013;Odum, Ward, Barnes, & Burke, 2006;Rodriguez & Thompson, 2015;Stahlman & Blaisdell, 2011;Stokes, 1995;Stokes, Mechner & Balsam, 1999;Ward, Kynaston, Bailey, & Odum, 2008). Nevertheless, a few researchers (Barba, 2015;Epstein, 2014;Holth, 2012;Machado, 1989Machado, , 1992Machado, , 1993Machado, , 1997Machado & Tonneau, 2012;Marr, 2012) have raised the question of whether direct reinforcement of variability is the most satisfactory view or whether the variability in these experiments is more effectively or pragmatically considered as a derivative of other procedural characteristics.…”
mentioning
confidence: 97%
“…Another important finding in the present study is that behavioral variability and repetition can be brought under discriminative stimulus control. Such stimulus control has already been reliably demonstrated in animal subjects (e.g., Denney & Neuringer, ; Doughty & Galizio, ; Galizio et al, ), but finding the same effect in applied settings has presented more of a challenge. Previous research has demonstrated discriminated variable responding in children with ASD (e.g., Brodhead et al, ), but it is unclear to what extent stimulus conditions must differ to promote discrimination in individuals with ASD.…”
Section: Discussionmentioning
confidence: 85%